Predictive effect of phubbing and life satisfaction on depression symptoms in adults - Parmaksız, İzzet (Journal of Dependence, 2021)
Objective: Phubbing, defined as being busy on the phone by ignoring people, and life satisfaction, which appears as a person's attitude to life, also manifest themselves as variables that affect our mental health. The aim of this study was to determine the predictive effect of phubbing and life satisfaction on the depression symptoms level of the individual.Method: The study group of the research consists of 756 adults (51.7% Female, 48.3% Male) living in Central Anatolia. The data of the study were collected using the Phubbing Scale, Beck Depression Scale, Life Satisfaction Scale and personal information form.Results: A significant negative relationship between phubbing and life satisfaction, a significant negative relationship between life satisfaction and depression symptoms, and a significant positive relationship between phubbing and depression symptoms were found. According to the preliminary analysis, depression symptoms scores do not significantly differentiate according to gender; differentiates significantly according to marital status, educational level and perceived personality traits. According to the results of hierarchical regression analysis, life satisfaction and phubbing behavior were found to be medium-level predictors of depression symptoms.Conclusion: Phubbing has been identified as a new descriptor for depression symptoms. Phubbing and life satisfaction are important predictors for depression symptoms.
Keywords: Depression symptoms; life satisfaction; phubbing